PENYULUHAN KEKERASAN TERHADAP ANAK DI KELURAHAN SEBANGAU - Sentosa, Alfrid; Rosmawiah, Rosmawiah; Norsandi, Dedy; Karya, Betty; Marni, Marni; Aprilyansyah, Mahdi Surya; Manya, Manya (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Violence against children is a serious problem that can interfere with children's physical, mental, and emotional development. In Sebangau Village, violence against children is still an issue that needs to be addressed comprehensively. This journal aims to explore counseling on violence against children in the region, by highlighting statistical data, case examples, and efforts that have been made to increase public awareness. Through this analysis, it is hoped that more effective strategies can be found in dealing with and preventing violence against children in Sebangau Village. Violence against children does not only have an impact on individuals, but also on society as a whole. When children experience violence, they are at risk of various mental health problems, such as depression, anxiety, and post-traumatic stress disorder (PTSD). In addition, children who are victims of violence tend to have difficulties in social interaction and learning, which can ultimately affect their future. In Sebangau Village, statistical data shows that the level of violence against children is still quite high. According to a report from the Women and Child Protection Office, there has been an increase in cases of violence against children in recent years. This shows that there is an urgent need to increase efforts to prevent and handle violence against children in the region. Overall, handling violence against children in Sebangau Village requires a holistic approach and involves all elements of society. By raising awareness, providing education, and building support networks, it is hoped that violence against children can be minimized and children can grow up in a safe and supportive environment. Through joint efforts, we can create a better future for future generations